Code Switching in Pulutan Lor As The Reflection of Bilingualism - Nibros Hassani; Maulida Swastuti; Sari Famularsih (Hasanuddin University, 2019)
In the multilingual region or community, certain social components influence language use. Moreover, in code-switching case, people sometimes switch code within a domain or social situation including the arrival of a new person and when there is some obvious change in the situation. Pulutan Lor as one of the little region in Salatiga, Central Java has got the arrival of many students since the built of new campus although they are not nameable as the permanent resident. This study aims to observe (i) How these newcomers in Pulutan Lor can give impact to society’s choice in using language (ii) What is the language used in the code-switching by the people in Pulutan. The methodology used is qualitative. The findings show (i) English is dominantly used in the code-switching, secondly is Javanese, and the last is Bahasa Indonesia (ii) The newcomers in Pulutan give impact at how society uses language even in casual conversation which is reflecting bilingualism.